Assessment of the 9p21.3 locus in severity of coronary artery disease in the presence and absence of type 2 diabetes - Rivera, Natalia V; Carreras-Torres, Robert; Roncarati, Roberta; Viviani-Anselmi, Chiara; De Micco, Francesca; Mezzelani, Alessandra; Koch, Werner; Hoppmann, Petra; Kastrati, Adnan; Stewart, Alexandre F; Chen, Li; Roberts, Robert; et al. (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background The 9p21.3 locus is strongly associated with the risk of coronary artery disease (CAD) and with type 2 diabetes (T2D). We investigated the association of 9p21.3 variants with severity of CAD (defined by the number of vessel diseased [VD]) in the presence and absence of T2D. Methods We tested 11 9p21.3-variants for association in a white Italian study (N = 2,908), and carried out replication in 2 independent white populations, a German study (N = 2,028) and a Canadian Study (N=950). SNP association and permutation analyses were conducted. Results We identified two 9p21.3-variants, rs4977574 (P < 4×10-4) and rs2383207 (P < 1.5×10-3) that were associated with severity of CAD in subjects without T2D. Association of rs4977574 with severity of CAD was confirmed in the Canadian Study. Results from subgroup analysis among patients with T2D showed an interaction between rs10738610 and T2D with P = 4.82×10-2. Further investigation showed that rs10738610 (P < 1.99×10-2) was found to be significantly associated with severity of CAD in subjects with T2D. Conclusions The 9p21.3 locus is significantly associated with severity of CAD. The number of associations of 9p21.3 variants with severity of CAD is variable to the presence and absence of T2D. In a CAD-susceptible region of 115 kb, there is only one variant associated with the severity of coronary vessel disease in the presence of type 2 diabetes.